Reflections on my bittersweet journey as a UiTM Pharmacy student / Nur Ainin Sofiya Mohamad Irwan - Mohamad Irwan, Nur Ainin Sofiya (Faculty of Pharmacy, 2023)
How time flies, with just a few months until graduation. For that, let me take you down memory lane about my experiences as a pharmacy student at UiTM. I am proud to be one of their undergraduates because our faculty has the largest infrastructure and its lecturers are excellent role models. May 2019 was the day I was filled with excitement and enthusiasm when I attended my entry interview at this university. Flashing back a bit further, upon finishing my foundation year, I prepared myself for the interview. With everything geared up, I took the interviewer along my aspirational path and pictured how this course could benefit me and, in return, what the university could gain upon my graduation. It was an exhilarating moment when, a month later, I passed the interview and returned to UiTM as a tertiary student, all excited to pursue my dream of becoming a successful pharmacist in the future.